2021
DOI: 10.1186/s13048-021-00889-8
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA SNHG20 promotes migration and invasion of ovarian cancer via modulating the microRNA-148a/ROCK1 axis

Abstract: Background Ovarian cancer (OC) is characterized by early metastasis and poor prognosis, which threatens the health of women worldwide. Small nucleolar RNA host gene 20 (SNHG20), a long noncoding RNA (lncRNA), has been verified to be significantly up-regulated in several tumors, including OC. MicroRNA-148a (miR-148a)/rho-kinase1 (ROCK1) axis plays an important role in the modulation of tumor development. However, whether SNHG20 can regulate OC progression through miR-148a/ROCK1 axis remains uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…ROCK1 regulates cellular processes such as actomyosin contractility, focal adhesion assembly, cytokinesis, and cell proliferation [6]. Accumulating evidence suggests that dysfunction of ROCK1 contributes to various cancers, including bladder [7], breast [8], ovarian [9], gastric [10], colon [11] and ovarian cancers [12]. Similarly, our study showed that ROCK1 is highly expressed in human LSCC tissues, and high expression of ROCK1 correlates with advanced stage and poor survival prognosis of LSCC patients.…”
Section: Introductionsupporting
confidence: 68%
“…ROCK1 regulates cellular processes such as actomyosin contractility, focal adhesion assembly, cytokinesis, and cell proliferation [6]. Accumulating evidence suggests that dysfunction of ROCK1 contributes to various cancers, including bladder [7], breast [8], ovarian [9], gastric [10], colon [11] and ovarian cancers [12]. Similarly, our study showed that ROCK1 is highly expressed in human LSCC tissues, and high expression of ROCK1 correlates with advanced stage and poor survival prognosis of LSCC patients.…”
Section: Introductionsupporting
confidence: 68%
“…Moreover, a a multi-label fusion collaborative matrix factorization (MLFCMF) approach was proposed for predicting lncRNA-disease associations, especially, their method finally obtains an AUC value of 0.8612 [ 32 ]. In addition to the above bioinformatics studies, the role of most lncRNAs in OC cell lines has also been explored, such as MSC-AS1 [ 33 ], TONSL-AS1 [ 34 ], and SNHG20 [ 35 ], etc. However, lncRNAs participating in risk signature have not been well explored in OC, and this suggests that our study is an indicator for Vivo and Vitro assays in the future.…”
Section: Discussionmentioning
confidence: 99%
“…LncNBAT1 represses the transcriptional activity of signal transducer and activator of transcription 1 (STAT1) to attenuate apolipoprotein B mRNA editing enzyme catalytic subunit 3 A (APOBEC3A) expression, which mediates chemoresistance in DLBCL cells [ 25 ]. The lncRNA SNHG20 has been demonstrated to play oncogenic roles in many cancers, including oral squamous cell carcinoma [ 26 ], ovarian cancer [ 27 ], colorectal cancer (CRC) [ 28 ], cervical cancer [ 29 ], lung cancer [ 10 ], glioma [ 11 ] and hepatocellular carcinoma [ 30 ]. However, its role in haematological diseases, especially DLBCL, has never been studied.…”
Section: Discussionmentioning
confidence: 99%